2015
DOI: 10.1002/ijc.29933
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of heme oxygenase‐1 as a novel immune regulator of neuroblastoma

Abstract: Heme oxygenase (HO)21 catalyzes the degradation of cytotoxic heme into biliverdin and blocks antitumor immune responses, thus protecting cancer against host defense. Whether this scenario also applies to neuroblastoma (NB), the most common extracranial solid childhood tumor, is not known. Here, we demonstrate for the first time a prognostic relevance of HO-1 expression in samples from NB patients and show that targeting of HO-1 prevents both cancer resistance against cellular stress and immune escape in the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Mice were divided into seven groups, five mice in each group per cage and kept in standard individually ventilated cages in an animal facility under standardized conditions (12 h light/dark cycle, 21–24°C, humidity of 50–60%) with food and water ad libitum . For the in vivo treatment, zinc protoporphyrin IX (ZnPPIX) (Fest et al, ) and CORM‐2 were dissolved in DMSO at a concentration of 10 and 50 mg·mL −1 , respectively, and further diluted in PBS before injection. The final dosages for ZnPPIX and CORM‐2 were 1.64 and 8 mg·kg −1 (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Mice were divided into seven groups, five mice in each group per cage and kept in standard individually ventilated cages in an animal facility under standardized conditions (12 h light/dark cycle, 21–24°C, humidity of 50–60%) with food and water ad libitum . For the in vivo treatment, zinc protoporphyrin IX (ZnPPIX) (Fest et al, ) and CORM‐2 were dissolved in DMSO at a concentration of 10 and 50 mg·mL −1 , respectively, and further diluted in PBS before injection. The final dosages for ZnPPIX and CORM‐2 were 1.64 and 8 mg·kg −1 (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…In addition, T regs recruitment is increased in HO-1-dependent manner in 4T1 breast cancer and in tumor-bearing mice [146] and HO-1 expression in cancer cells is related to the increased generation of IL-10 responsible for keeping DC immaturity [147,148]. …”
Section: Ho-1 In Tumor Immune-escapementioning
confidence: 99%
“…Moreover, in neuroblastoma samples, the univariate Kaplan–Meier analysis revealed that high HO-1 RNA expression levels are associated with an unfavorable prognosis [147] and, in histological samples of human glioma, HO-1 expression was higher in comparison to non-malignant brain tissue [187] with no differences among the various tumor grades. However, HO-1 protein expression was associated with a worse prognosis of grade II and III astrocytoma patients [187].…”
Section: Ho-1 As a Possible Biomarkermentioning
confidence: 99%
“…The expression of HO-1 increases the production of CO, iron and biliverdin, enhances cell protection, resists apoptosis, promotes cell proliferation, reduces inflammatory response and so on [13]. High HO-1 expression can induce the resistance of tumor cells such as neuroblastoma [14,15]. Our group has also published a series of articles about the relationship between HO-1 and leukemia in recent years [16][17][18].…”
Section: Introductionmentioning
confidence: 93%